IMPLEMENTASI LIFE SKILL UNTUK MENUMBUHKAN JIWA KEWIRAUSAHAAN DI MA NU 01 LIMPUNG KABUPATEN BATANG - MUNIROCH, MUNIROCH; NURKOLIS, NURKOLIS; HARYATI, TITIK (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
The purpose of this study is to describe and analyze the process of planning, implementing, and evaluating life skills to foster an entrepreneurial spirit in MA NU 01 Limpung, Batang Regency. This study uses a qualitative method with a case study approach in MA NU 01 Limpung. Data were collected through in-depth interviews with the head of the madrasah, deputy head of the madrasah, life skill mentor teachers, life skill tutors, students, and alumni. In addition, observation and documentation were carried out to obtain an overview of the program implementation process. Data analysis techniques were carried out by collecting data, reducing data, presenting data, and drawing conclusions. The validity test of the data used triangulation of sources and methods. The results of the study indicate that the implementation of life skills to foster an entrepreneurial spirit in MA NU 01 Limpung, Batang Regency was carried out through: 1) planning includes: setting goals through coordination between stakeholders, determining strategies in selecting prospective partners and tutors, determining socialization procedures, determining schedules, and monitoring plans, determining learning methods, and planning budget management; 2) implementation includes: implementation of activities according to schedule, including life skills of culinary arts, fashion and make-up, providing motivation and guidance from tutors, utilization of facilities and infrastructure, application of learning methods, monitoring of activity processes, communication and coordination, and appreciation; 3) evaluation includes: analysis of internal factors (quality of tutors, supervising teachers, facilities, and administrative support), analysis of external factors (support from parents), measurement of program performance (achievement of goals, student involvement, and skill improvement, and identification of corrective actions. The conclusion of this study is that the implementation of life skills to foster an entrepreneurial spirit in MA NU 01 Limpung, Batang Regency, especially for the types of culinary arts, fashion, and make-up, has been implemented well, this can be seen from the high level of student participation and the large number of alumni of the three types of life skills who are involved in the world of entrepreneurship. ABSTRAKTujuan penelitian adalah untuk mendeskripsikan dan menganalisis tentang proses perencanaan, pelaksanaan, dan evaluasi life skill untuk menumbuhkan jiwa kewirausahaan di MA NU 01 Limpung kabupaten Batang. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus di MA NU 01 Limpung, Data dikumpulkan melalui wawancara mendalam dengan kepala madrasah, wakil kepala madrasah, guru pembina life skill, tutor life skill, siswa, dan alumni. Selain itu, observasi dan dokumentasi dilakukan untuk mendapatkan gambaran mengenai proses implementasi program. Teknik analisis data dilakukan dengan cara pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Uji keabsahan data menggunakan triangulasi sumber dan metode. Hasil penelitian menunjukkan bahwa implementasi life skill untuk menumbuhkan jiwa kewirausahaan di MA NU 01 Limpung kabupaten Batang dilakukan melalui: 1) perencanaan meliputi: menetapkan tujuan melalui koordinasi antar stakeholder, menentukan strategi dalam memilih calon mitra dan tutor, menetapkan prosedur sosialisasi, penentuan jadwal, dan rencana pemantauan, menentukan metode pembelajaran, serta merencanakan pengelolaan anggaran; 2) pelaksanaan meliputi: pelaksanaan kegiatan sesuai jadwal, diantaranya life skill tata boga, tata busana dan tata rias, pemberian motivasi dan pembimbingan dari tutor, pemanfataan sarana prasarana, penerapan metode pembelajaran, pemantauan proses kegiatan, komunikasi dan koordinasi, serta apresiasi; 3) evaluasi meliputi: analisis faktor internal ( kualitas tutor, guru pembina, fasilitas, dan dukungan administrasi), analisis faktor eksternal (dukungan dari orang tua), pengukuran kinerja program (pencapaian tujuan, keterlibatan siswa, dan peningkatan keterampilan, dan identifikasi tindakan perbaikan. Kesimpulan dari penelitian ini adalah implementasi life skill untuk menumbuhkan jiwa kewirausahaan di MA NU 01 Limpung kabupaten Batang terutama untuk jenis tata boga, tata busana, dan tata rias sudah dilaksanakan dengan baik, hal ini terlihat dari tingginya tingkat partisipasi siswa dan banyaknya jumlah alumni life skill tiga jenis tersebut yang terjun dalam dunia wirausaha.